Management of immune-related adverse events resulting from immune checkpoint blockade. Issue 3 (4th March 2019) - Baroudjian, Barouyr; Arangalage, Dimitri; Cuzzubbo, Stefania; Hervier, Baptiste; Lebbé, Celeste; Lorillon, Gwenael; Tazi, Abdellatif; Zalcman, Gerard; Bouattour, Mohamed; Lioté, Frédéric; Gautier, Jean-François; Brosseau, Solenn; et al.
ABSTRACT: Introduction : Immune checkpoint inhibitors (ICI) are now a standard of care in the treatment of many cancers leading to durable responses in patients with metastatic disease. These agents are generally well tolerated but may lead to the occurrence of immune-related adverse events (irAEs). As any organ may be affected, clinicians should be aware of the broad range of clinical manifestations and symptoms and keep in mind that toxicities may occur late, at any point along a patient's treatment course. Although the most common irAEs are rarely severe, some of them may be associated with great morbidity and even become life-threatening. The rate of occurrence, type and severity of irAEs may vary with the type of ICI; thus, grade 3 and 4 irAEs are reported in more than 55% of patients treated with the combination of ipilimumab 3 mg/kg and nivolumab 1 mg/kg. Area covered : This review presents the management of irAEs resulting from checkpoint blockade, with a focus on rare irAEs. Expert commentary : With the development of immuno-oncology and the expanding role of ICI, physicians have learnt to diagnose and treat most of the irAEs that can occur. This review provides an overview of current guidelines, previously published studies and our multidisciplinary team based practices.